A Novel Multi-level Bi-directional DC/DC Converter for Inductive Power Transfer Applications - Colak, Kerim; Asa, Erdem; Czarkowski, Dariusz; Komurcugil, Hasan (IEEE, 2015)
In this study, a novel multi-level type bidirectional half-bridge inverter for wireless power transfer applications is presented. The proposed converter provides high power application by splitting the voltage in each switch. The converter topology is explored to reveal the maximum efficiency points with a variable phase-shift function between the dual active level (DAL) switches. The analysis of the converter is provided in terms of variable load and coupling co-efficient factor at a constant switching frequency. A 1 kW contactless system is designed with an output of 100 V by testing the different load conditions at an 8 inch gap between coils. Experimental results are clearly indicate that the demonstrated system, which has an average efficiency improvement of 3% with an optimized phase shift between switches, offers higher efficiency in comparison to conventional multi-level topologies.
41st Annual Conference of the IEEE-Industrial-Electronics-Society (IECON) -- NOV 09-12, 2015 -- Yokohama, JAPAN
Keywords: bi-directional; dual active; multi-level; phase-shift; resonant converter; wireless energy